2009
DOI: 10.1007/s11104-009-9966-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and modelling C and N mineralization kinetics of catch crop residues in soil: parameterization of the residue decomposition module of STICS model for mature and non mature residues

Abstract: C and N mineralization kinetics of 25 catch crop (CC) residues, whose organic C:N ratio varied from 9.5 to 34.0, were studied during soil incubations under controlled conditions. Decomposition rates were rather similar for the different CC residues, 59% to 68% residue-C being mineralized after 168 days incubation. C mineralized during the first weeks was mainly correlated to the soluble C content of the residue. N mineralized from CC residues was much more variable (−4.9 to +38.0 mg N g −1 added C at day 168),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 44 publications
3
64
0
Order By: Relevance
“…In contrast to mineral fertilizers, nutrients accumulated by cover crops are released progressively and cover crop mineralization can be coordinated with subsequent crop needs. For this purpose, C/N ratio can be used as an indicator of the dynamics and the rate of mineralization (Justes et al 2009). With C/N ratio values above 26, it has been shown that a net immobilization of N by soil microorganisms occurs within the first weeks (Justes et al 2009).…”
Section: Influence Of Plant Traits On Nutrient Uptakementioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to mineral fertilizers, nutrients accumulated by cover crops are released progressively and cover crop mineralization can be coordinated with subsequent crop needs. For this purpose, C/N ratio can be used as an indicator of the dynamics and the rate of mineralization (Justes et al 2009). With C/N ratio values above 26, it has been shown that a net immobilization of N by soil microorganisms occurs within the first weeks (Justes et al 2009).…”
Section: Influence Of Plant Traits On Nutrient Uptakementioning
confidence: 99%
“…For this purpose, C/N ratio can be used as an indicator of the dynamics and the rate of mineralization (Justes et al 2009). With C/N ratio values above 26, it has been shown that a net immobilization of N by soil microorganisms occurs within the first weeks (Justes et al 2009). Mineralization rate is also reduced and strong pre-emptive competition can occur (Thorup-Kristensen and Dresbøll 2010).…”
Section: Influence Of Plant Traits On Nutrient Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…According to many researchers, mineralization and immobilization of incorporated organic matter are influenced by its chemical composition, especially C:N (Justes et al, 2009). In our study, the C:N in the above ground mass of various catch crops was favourable for decomposition and varied little depending upon the type of crops.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of only catch crops' biomass led to N min increase by 6.31-9.90 mg kg -1 , meanwhile when straw had been spread -by 7.18-12.40 mg kg -1 of soil, compared to that in the autumn. N immobilization occurs only during a limited period of time, sufficient to prevent part of the mineral N pool from leaching, and net N mineralization can be expected during the subsequent cropping season, thus enhancing synchronization of N supply and demand (Trinsoutrot et al, 2000;Vinten at al., 2002;Justes et al, 2009). Another factor, which determines decomposition is soil properties, i.e.…”
Section: Discussionmentioning
confidence: 99%